Consumer savings behaviour at low and negative interest rates - Marco Felici; Geoff Kenny; Roberta Friz (European Central Bank (ECB), 2022)
We study interest rates transmission to savings at low and negative rates. Exploiting cohorts of consumers from a data-rich multi-country survey, we show how the strength of interest rate transmission to savings varies with the level of nominal interest rates. This response is positive when interest rates are high but declines steadily at lower levels. At very low levels, there is evidence that the savings response may even reverse sign. Such a "savings' reversal" is consistent with the behavioural evidence on money illusion as well as with a negative signalling effect from policy announcements in a liquidity trap and may weaken the direct stimulatory effects from very low and negative rates. Consistent with this, the reversal appears to be causally related to central bank information shocks and concentrated among older consumers and consumers with lower educational attainment.
Keywords: D12; D84; E21; E31; E52; 330; Savings; Nominal Interest Rates; Consumer Survey; Liquidity Trap; Euro Area